(untitled) (Journal of Preventive and Social Medicine, 2022)
Background: Children never faced a pandemic situation. For this situation children’s lives are being affected, including their daily routine. This situation could have influenced both bad or good habit. One of the most alarming issue was their food consumption pattern during lockdown at home. Objective: To assess an English medium school children’s food consumption habit during COVID-19 lockdown. Materials and methods: This cross-sectional study was carried out about one of the English medium school children’s eating habits during the COVID-19 lockdown in Bangladesh. Online questionnaire was developed and delivered to the care giver of the children’s. Total 130 caregivers and 223 children were selected purposively. The study period was 1st October 2020 to February 2021. Results: Distribution of the children according to the sex, female (70.4%) were more than male and ten to eleven years’ children (40.8%) were more. Educational background of caregivers found, graduation (76.2%), only 48.5% care givers sometimes did physical activity, monthly family income more the two lacs (66.2%), homemaker (71.6%) and 77.7% of them cooked food with the help of housemaid. Chocolate, milk product, meat and fast food intake is alarmingly high, found in seven days’ food intake chart. 60% children take extra food two times in a day, 50% of that food was homemade and online ordered. Foods were ordered 2-3 times per week by 44.6% caregivers and mostly ordered items were fast foods (66.2%). 63.1% children were found overweight. There was significant association between frequent online food order and change body shape of the child (p=.04) and monthly income and how many time children’s intake extra food in a day (p=.01). Conclusion: Schools were run in online basis. Parents were responsible for their children food intake throughout the whole day. It was challenging for the parents. JOPSOM 2021; 40(2):32-37